Recanalization and Reperfusion Therapies of Acute Ischemic Stroke: What have We Learned, What are the Major Research Questions, and Where are We Headed? - Gomis, Meritxell; Dávalos, Antoni (Frontiers in Neurology, 2014)
Two placebo-controlled trials have shown that early administration of intravenous recombinant tissue plasminogen activator (rt-PA) after ischemic stroke improves outcomes since 4.5h after symptoms onset; meanwhile another six trials cannot demonstrate it. We also know from the analysis of the pooled data that benefit from treatment decreased as time from stroke onset to start the treatment increased. In addition to time, another important point is patient selection through multimodal imaging, combining data from artery status and salvageable tissue, but nowadays, randomized controlled trials (RCT) cannot demonstrate outcomes benefit of neuroimaging mismatch selection far away from 4.5h from symptoms onset. Focusing in cases of large arterial occlusion we know that recanalization is crucial, so an interesting approach it has been the use of endovascular treatment. The use of intraarterial thrombolysis was tested in two small RCT that demonstrated clear benefit in terms of higher recanalization and also in clinical outcomes. But a new paradigm of stroke treatment may have begun with mechanical thrombectomy. In this field, Merci devices have been overcome by the fully deployed closed-cell self-expanding stents (stent-triever). However even thought the highly rate of recanalization obtained with the stent retrievers compared with the other recanalization treatments, the use of those devices cannot demonstrate clear better outcomes. Thus futile recanalization occurs when successful recanalization fails to improve functional outcome. Recently three randomized controlled trials, Synthesis, IMS-III, and MR-Rescue, have not been demonstrated clear benefit of endovascular treatment. Probably this trials fails in their design in order to prove the superiority of endovascular treatment due to it did not use an optimal target populations, the vascular status were not evaluated in all patients, a relatively high rates of patients did not have enough mismatch, time from baseline n